2006
DOI: 10.1086/501370
|View full text |Cite
|
Sign up to set email alerts
|

New Complexities in the Genetics of Stuttering: Significant Sex-Specific Linkage Signals

Abstract: Stuttering is a speech disorder long recognized to have a genetic component. Recent linkage studies mapped a susceptibility locus for stuttering to chromosome 12 in 46 highly inbred families ascertained in Pakistan. We report here on linkage studies in 100 families of European descent ascertained in the United States, Sweden, and Israel. These families included 252 individuals exhibiting persistent stuttering, 45 individuals classified as recovered from stuttering, and 19 individuals too young to classify. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 41 publications
3
85
1
4
Order By: Relevance
“…[8][9][10][11][12][13] Although the subjacent nucleus of PDS still remains unclear, there is a strong body of evidence suggesting that PDS is a hereditary disorder which manifestation is a dysfunction in central motor speech control. [14][15][16][17][18][19][20] In Freed's21 model, the neuromuscular processing can be investigated through evidence given by the behavior of muscles that contribute to normal speech production. If any of these traces are in some way compromised, the motor system will be negatively affected.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Although the subjacent nucleus of PDS still remains unclear, there is a strong body of evidence suggesting that PDS is a hereditary disorder which manifestation is a dysfunction in central motor speech control. [14][15][16][17][18][19][20] In Freed's21 model, the neuromuscular processing can be investigated through evidence given by the behavior of muscles that contribute to normal speech production. If any of these traces are in some way compromised, the motor system will be negatively affected.…”
Section: Introductionmentioning
confidence: 99%
“…Half of the stutterers had a family history, and risk to first degree relative was 15%. Several large families with multiple individuals were affected by stuttering [10][11][12][13][14][15].…”
Section: Genetic Evidence Of Stutteringmentioning
confidence: 99%
“…These puzzling clinical features, and the fact that stuttering has its origin in the brain, hinder researchers from investigating the neural basis of stuttering. However, several genetic studies such as twin, adoption, and segregation studies have suggested that this disorder occurs by the inheritance of gene mutations [9][10][11][12][13][14][15][16]. Genetic evidence presented by several approaches, in particular, genome-wide linkage analysis have shed light on these causative genes.…”
Section: Introductionmentioning
confidence: 99%
“…The likely source of stuttering that is genetically transmitted is the inability to automatically update internal models (related to the dynamics of the execution motor control effector system), leading to the sensorial consequences of movement repetition or blockage, preventing the completion of the motor order issued, and causing a continuous reinitialization of the system. Stuttering symptomatology (involuntary disruptions of speech flow) changes speech naturalness, making communication stressful, challenging, and frustrating (13,14,15,16,17,18) . One of the tests used to assess speech motor production is diadochokinesis (DDK), used to determine the speed and regularity of the movements of the jaw, lips, and tongue.…”
Section: Introductionmentioning
confidence: 99%